THE LEXICAL ITEM WORD IN EXPERIMENTAL RESEARCH (Philological Studies, 2019)
The paper presents an experimental research which singles out semantic components of the lexical item word in linguistic consciousness of modern students. In an associative test with the lexical item word as a stimulus 371 reactions were produced. The total set of the received associates was classified into four groups: linguistic, cultural, social and emotional reactions. The reasons for actualizing the concept of the lexical item word are revealed; the main reason proves to be the informant's speciality.
Keywords: free associative test, an associate, semantic component of word meaning, lexical groups